Addiction of Students through usage of Smart Phone and its Impact on Human Resources in India: A Preliminary Survey (Journal of Pharmaceutical Negative Results, 2023)
Background: The evolution of mobile phones from basic to smart phones has spread technology across age, gender, and region. Mobile phone addiction has become a behavioural addiction among students. Anxiety and Fear of Missing out cause university students to check their phones 150 times a day, a new study finds. People also use smartphones for non-calling purposes, such as accessing social networking sites, using Google, and watching YouTube videos. Aims & Objectives: The study is to assess the level of addiction to smart phone Usage, and its associated implication on youth from selected colleges in Chennai City. Materials and Methods: Over the period of six months the data pertaining to the study area was collected through a structured questionnaire. A total of 200+ samples were collected factors arrtibuting to usage of mobiles using the google forms from selected colleges at Chennai. Descriptive and inferential statistics would be calculated for the data set to draw meaningful inferences out the data and to draw conclusion. Preferably Correlation between - no. of hours spent on social media usage, gaming, OTT(Over-the-Top), change in lifestyle (Behavioural change among youths) due to smartphone usage addiction and Percentage Analysis, Correlation and Chi-square test would be carried out to know the exact relationship among the variables using SPSS v.21. Results: There is a negative correlation exists between time for study and time dedicated for study which means students are not concentrating and positive relationship exist between time for study to studies besides games which means playing games while study. Negative relationship exists between time for study to skipping meal and frequently checking mobile phone for notifications. Concentrate on studies besides games to obedient to parents is found to be positively correlated and avoiding social events, skipping meal and frequency of checking mobile for alters is negatively correlated, which means studies beside playing games is a new way of learning it goes side by side. Students are not ready to participate in social events, skip meal and not like to avoid frequently checking their mobile for alerts/ notifications. Conclusion and Suggestions: Gender and Time spent on social media, Attributes to check and use mobile frequently, Time Spent on Gaming apps, Time spent on favourite social media app, Time spent on OTT apps are associated with each other. Irrespective of gender the Time spent on the above things is same.